Power systems expansion planning with time-varying CO2 tax. (September 2020) - Pereira, Andrés; Sauma, Enzo
Abstract: This article analyzes the effects of implementing a two-stage carbon tax on a ten-year power expansion planning model. The timing effect of the tax is analyzed by studying the costs, capacity investments, economic dispatch, and CO 2 emissions in fixed (flat) and two-stage tax schemes. Results show that, under the absence of political economy constraints, the most cost-effective solution is to have a low CO 2 tax in the first stage and an optimal (higher) tax in the final stage. However, early actions can be justified depending on how relevant the policy maker considers the beneficial economic and not economic outcomes of a higher first-stage tax. Consequently, focusing on a final-period goal may not be the best way of facing the global warming problem, if emissions saved early have an important value when preventing the consequences of Climate Change.